The Conference of the Birds: The Selected Sufi Poetry of Farid ud-Din Attar by Raficq Abdulla (Northampton, MA: Interlink Books, 2003. 93 pages.) (American Journal of Islam and Society, 2005)
In medieval Islamic civilization, poetry was widely acknowledged to be themost intimate vessel for conveying Sufism’s hidden truths. The spiritualstates and stations traversed by adepts along an ascending path to the realityof God’s unity largely defies simple descriptions into ordinary prose oreveryday language. The subtleties necessary to evocatively describe a spiritualjourney that is, by its very essence, ineffable, necessitates a linguisticmedium that could at once reveal secrets of inner contemplation and mysticalperception while simultaneously concealing such information from the“uninitiated” behind the exoteric understanding of the same work of literature.Persian poetry, with its unique capacity for metaphorical symbolism,puns, and paradoxes, thus emerged by the seventh/thirteenth century as anunparalleled vehicle for expressing the mystical experience.The most dramatic expression in all of Persian mystical literature of thisspiritual journey is the allegorical poem Mantiq al-Tair (best translated as“The Speech of the Birds”) by Farid al-Din `Attar (d. 627/1229), whichrecounts the initiatory voyage of a group of birds through seven valleys tothe palace of the mythical king-bird Simurgh, symbol of the Divine,enthroned atop the cosmic mountain Qaf.In addition to the book currently under review, `Attar’s masterpieceinspired other renditions into English, including an abbreviated and freelyreworked edition by Edward FitzGerald, The Bird-parliament (1903); R. P.Masani’s prose translation of half the original poem’s 4,600 lines, TheConference of the Birds (1924); the incomplete prose version by C. S. Nott,The Conference of the Birds (1954), which was prepared from Garcin deTassy’s nineteenth-century French translation, Le Langage des oiseaux, and,as such, is obscured by an intervening third language; Afkham Darbandi andDick Davis’ Penguin Classics edition The Conference of the Birds (1984),which represents the poem’s first complete English translation (minus theinvocation and epilogue), is based on the oldest extant manuscripts, and isskillfully rendered into heroic couplets pleasingly faithful to the letter andspirit of `Attar’s allegory; and Peter Avery’s determinedly literal translation,The Speech of the Birds (1998), whose 560-page opus includes 120 pages ofenriching endnotes on `Attar’s use of Qur’anic imagery and the hadith ...